HUBUNGAN PERILAKU PANTANG MAKAN DENGAN WAKTU PENYEMBUHAN LUKA PASIEN POST SECTIO CAESAREA - Heni Purwaningsih; Dyah Ambarningtyas; Gipta Galih Widodo (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2020)
ABSTRACTBackground of Study: One of the factors that can affect the wound healing of post-SC patients is eating abstinence. Tarak (Abstinence) to the food should not be done by post operative mother sectio caesaria because it can slow the healing process of stitches wound. The purpose of this research is to know the difference of abstinence behavior and the wound healing time of post sectio caesarea patient at Ken Saras Hospital and Kusuma Ungaran Hospital. Methods: The research design is a comparative method with cross sectional approach. The population of this study postpartum mother of SC in Ken Saras and Kusuma Hospital with the  number  of  samples  66  respondents  using  purposive  sampling  technique  and  data collection tools using questionnaires. Data analysis used chi square test. Result: The results showed the abstinence behavior of patients post sectio caesarea day 7 categories abstinence 62,1% and wound healing time patients post sectio caesarea day 7 fast category 59,1%. There was an association of abstinence-eating behavior with wound healing time of post-sectio caesarea patients, with p value of 0,000 (α = 0,05). Conclusion: Preferably post sectio caesarea mothers increase abstinence behavior by for example by making a menu schedule recommended by medical personnel and asking for support from the family related menu they should provide so that the healing time can be in line with expectations. Keywords: Abstinence Behavior, Healing Wound Time, Patient Post Sectio Caesarea